IPTEKS BAGI MASYARAKAT KELOMPOK PETERNAK AYAM KAMPUNG PADA PETERNAKAN DI NEGERI RUTONG KOTA AMBON - Papilaya, Bercomien J; Rajab, Rajab; Sarfan, Riri (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
Native chicken farms can support the community's economy, there are many in rural areas and are generally traditional. Human intervention in maintenance is limited to ownership, housing and limited feed. The negative impact of maintenance like this is low production. Objectives: 1. Increase chicken production, utilize fisheries and agricultural waste (sago dregs, cassava leaves, lamtoro leaves). 2. Increase the knowledge and skills of breeders on how to process feed ingredients and prepare rations. 3. Train and motivate farmers to improve maintenance systems and develop their livestock business. The target of this activity is a group of native chicken breeders (Dasawisma group). The success of this activity is measured through better farmer attention (80%) to the livestock being kept and better production. Treatment results on IbM livestock rations resulted in egg production and egg quality which were 25-40% better, and DOC weight was quite high compared to the extensive method (conventional feed). Groups can have increased knowledge about feed and applicable hatchery technology